Urban Resettlements in the Global South Lived Experiences of Housing and Infrastructure between Displacement and Relocation - Beier, Raffael; Spire, Amandine; Bridonneau, Marie (Taylor & Francis, 2021)
displacement; global south; housing; infrastructure; relocation; urban resettlements; pandemic; COVID-19